Evaluating Nuclear Nonproliferation Regime-Case Study: North Korea - Priamarizki, Adhi (Jurnal Ilmiah Hubungan Internasional, 2012)
This paper try to explain why a country refused to join the nuclear weapons nonproliferation regime. The main argument of this article is the failure of the nuclear weapons nonproliferation regime to create a state-nuclear negara abandon their nuclear weapons because the regime does not successfully complete the core problem that triggered the decision to develop nuclear weapons. The decision will be difficult to change when it is done in order to maintain domestic power in the country that has nuclear weapons. Moreover, the perception of threat also came from rival states with nuclear weapons or non-nuclear states in alliance with the nuclear state. This article uses a case study of North Korea to prove the argument the author.Keywords : nuclear weapon, nuclear nonproliferation regime, nuclear politics, North Korea, Juche